Slurry for thermal spraying and method for producing thermal spraying film using same

By adding dispersion medium to the spray slurry and meeting specific formula conditions, the common crack problems in spray plating films are solved, and the density and stability of the coating are improved.

CN119736574APending Publication Date: 2025-04-01FUJIMI INCORPORATED
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411349652.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-09-29
Filing Date
2024-09-26
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

In spray coatings formed by using spray slurry for spraying particles formed of oxides containing aluminum, cracks often occur.

Method used

By adding a dispersion medium to the spray slurry, it is ensured that the slurry meets the conditions of the specific formula (E×α)/D90<130, where E is the Young's modulus of the oxide, α is the linear thermal expansion coefficient, and D90 is the volume reference of the sprayed particles accumulated by 90% of the particle size.

Benefits of technology

By meeting the above conditions, cracks in the sprayed coating can be significantly reduced, and the density and stability of the coating can be improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005061973650000221
    Figure BDA0005061973650000221
  • Figure HDA0005061973660000011
    Figure HDA0005061973660000011
  • Figure HDA0005061973660000012
    Figure HDA0005061973660000012
Patent Text Reader

Abstract

The present invention relates to a slurry for thermal spraying and a method for producing a thermal spraying film using the same. [Problem] To provide a solution whereby it is possible to reduce cracks in a thermal spray coating film formed using a thermal spray slurry containing thermal spray particles formed from an oxide containing aluminum. One embodiment of the present invention relates to a thermal spray slurry containing thermal spray particles comprising an oxide containing aluminum and a dispersion medium, the thermal spray slurry satisfying formula (1) in which E is a Young's modulus [unit: GPa] of the oxide at a temperature of 25 DEG C, alpha is a linear thermal expansion coefficient [unit: ppm / K] of the oxide in a temperature range of 30 DEG C to 600 DEG C, and alpha is a linear thermal expansion coefficient [unit: ppm / K] of the oxide in a temperature range of 30 DEG C to 600 DEG C; and D90 represents a volume-based cumulative 90% particle diameter [unit: [mu] m] of the thermal spray particles. (1) (E * alpha) / D90 < 130.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a thermal spray slurry and a method for producing a thermal spray coating using the same. Background Art

[0002] Ceramic spray coatings are used in various applications depending on the characteristics of the ceramics they constitute. Japanese Patent Publication No. 2002-80954 discloses that a spray coating obtained by spraying a spray powder formed of a composite oxide containing aluminum and yttrium is suitable as a protective coating for components of a semiconductor device manufacturing device. Japanese Patent Publication No. 2013-531135 discloses that an aluminum oxide coating is used as a protective coating for components of a semiconductor device manufacturing device, and a plasma spraying method is cited as one of the techniques for making an aluminum oxide coating.

[0003] The ceramic spray coating can also be formed by spraying a slurry containing spraying particles. Japanese Patent Application Laid-Open No. 2007-298490 discloses forming an insulating ceramic body integrally with a solid electrolyte body by plasma spraying an insulating ceramic slurry containing an insulating ceramic such as alumina and a solvent onto a solid electrolyte body. Summary of the invention

[0004] However, the present inventors discovered that cracks may occur in the thermal spray coating while conducting research on a thermal spray coating formed using a thermal spray slurry containing thermal spray particles composed of an oxide containing aluminum.

[0005] Therefore, an object of the present invention is to reduce cracks in a thermal spray coating formed using a thermal spray slurry containing thermal spray particles composed of an oxide containing aluminum.

[0006] The present inventors have found that the characteristics of oxides containing aluminum are sometimes related to the generation of cracks in the thermal spray coating. In addition, the present inventors have surprisingly found that the specific particle size of thermal spray particles formed of oxides containing aluminum is related to the generation of cracks in the thermal spray coating.

[0007] Therefore, one aspect of the present invention relates to a thermal spraying slurry comprising: thermal spraying particles formed of an oxide containing aluminum and a dispersion medium.

[0008] The above-mentioned spraying slurry satisfies the following formula (1):

[0009] (E×α) / D90<130…(1)

[0010] In the above formula (1),

[0011] E is the Young's modulus of the oxide at 25°C [unit: GPa],

[0012] α is the linear thermal expansion coefficient of the aforementioned oxide in the temperature range of 30°C to 600°C [unit: ppm / K],

[0013] D90 is the volume-based cumulative 90% particle size of the thermal spray particles [unit: μm]. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 This is a surface observation image using a digital microscope of a thermal spray coating formed using the thermal spray slurry of Example 1 according to one embodiment of the present invention.

[0015] Figure 2 This is a surface observation image of a thermal spray coating formed using the thermal spray slurry of Comparative Example 1, taken with a digital microscope.

[0016] Figure 3 This is a surface observation image of a thermal spray coating formed using the thermal spray slurry of Comparative Example 2, taken with a digital microscope. DETAILED DESCRIPTION

[0017] Hereinafter, embodiments of the present invention will be described, but the present invention is not limited to the following embodiments only, and various modifications can be made within the scope of the claims. The embodiments described in this specification can be combined arbitrarily to form other embodiments.

[0018] In this specification, "X to Y" is used to include the numerical values ​​(X and Y) described before and after as the lower limit and upper limit, and means "more than X and less than Y". In addition, unless otherwise specified, the operation and measurement of physical properties are measured under the conditions of room temperature (20 to 25°C) / relative humidity 40 to 50% RH.

[0019] In the present specification, "A and / or B" means to include A, B individually and their combinations.

[0020] <Spraying slurry>

[0021] One aspect of the present invention relates to a thermal spray slurry comprising thermal spray particles formed of an oxide containing aluminum and a dispersion medium.

[0022] The above-mentioned thermal spraying slurry satisfies the following formula (1).

[0023] (E×α) / D90…130…(1)

[0024] In the above formula (1),

[0025] E is the Young's modulus of the oxide at 25°C [unit: GPa],

[0026] α is the linear thermal expansion coefficient of the aforementioned oxide in the temperature range of 30°C to 600°C [unit: ppm / K],

[0027] D90 is the volume-based cumulative 90% particle size of the thermal spray particles [unit: μm].

[0028] According to this embodiment, cracks in a thermal spray coating formed using a thermal spray slurry containing thermal spray particles composed of an oxide containing aluminum can be reduced. In this embodiment, by making the thermal spray slurry satisfy the above formula (1), cracks in a thermal spray coating formed using the thermal spray slurry can be reduced.

[0029] The reason is speculated to be that when the Young's modulus (E) at a temperature of 25°C and the linear thermal expansion coefficient (α) in the temperature range of 30°C to 600°C are respectively small, the stress generated during thermal contraction becomes smaller. Therefore, when the product of the Young's modulus (E) at a temperature of 25°C and the linear thermal expansion coefficient (α) in the temperature range of 30°C to 600°C is small, it becomes less likely to cause cracks in the sprayed coating. In addition, although the details are unclear, the inventors of the present invention have found that the volume-based cumulative 90% particle size (D90) has a high correlation with the generation of cracks in the sprayed coating, and the larger the volume-based cumulative 90% particle size (D90), the less likely it is to cause cracks in the sprayed coating. It is also speculated that when the above (1) is satisfied, the effect of reducing cracks in the sprayed coating is significantly improved according to their synergistic effect. It should be noted that this mechanism is based on speculation, and its correctness does not affect the technical scope of the present invention.

[0030] The calculated value on the left side of the formula (1) is not particularly limited as long as it is less than 130. Examples of the range of the calculated value on the left side of the formula (1) include 125 or less, 120 or less, 110 or less, 100 or less, 1 or more, 10 or more, 50 or more, 60 or more, 70 or more, 90 or more, 1 or more and less than 130, 10 or more and less than 130, 50 or more and less than 130, 60 or more and less than 130, 70 or more and less than 130, 90 or more and less than 130, 1 or more and less than 125, 10 or more and less than 125, 50 or more and less than 125, 60 or more and less than 125, 70 or more and less than 125, 90 or more and less. 125 or less, 1 or more and 120 or less, 10 or more and 120 or less, 50 or more and 120 or less, 60 or more and 120 or less, 70 or more and 120 or less, 90 or more and 120 or less, 1 or more and 110 or less, 10 or more and 110 or less, 50 or more and 110 or less, 60 or more and 110 or less, 70 or more and 110 or less, 90 or more and 110 or less, 1 or more and 100 or less, 10 or more and 100 or less, 50 or more and 100 or less, 60 or more and 100 or less, 70 or more and 100 or less, 90 or more and 100 or less, etc. When the thermal spraying particles are formed of aluminum oxide, the calculated value on the left side of the formula (1) is not particularly limited as long as it is lower than 130, and examples thereof include 125 or less, 1 or more, 10 or more, 50 or more, 60 or more, 70 or more, 90 or more, 100 or more, 110 or more, 120 or more, 1 or more and less than 130, 10 or more and less than 130, 50 or more and less than 130, 60 or more and less than 130, 70 or more and less than 130, 90 or more and less than 130, 100 or more and less than 130, 110 or more and less than 130, 120 or more and less than 130, 1 or more and less than 125, 10 or more and less than 125, 50 or more and less than 125, 60 or more and less than 125, 70 or more and less than 125, 90 or more and less than 125, 100 or more and less than 125, 110 or more and less than 125, 120 or more and less than 125, and the like.When the thermal spraying particles are formed of an oxide containing aluminum (Al) and yttrium (Y), the calculated value on the left side of the formula (1) is not particularly limited as long as it is less than 130. For example, it can be 125 or less, 120 or less, 110 or less, 100 or less, 1 or more, 10 or more, 50 or more, 60 or more, 70 or more, 90 or more, 100 or more, 110 or more, 120 or more, 1 or more and less than 130, 10 or more and less than 130, 50 or more and less than 130, 60 or more, Above and below 130, Above 70 and below 130, Above 90 and below 130, Above 100 and below 130, Above 110 and below 130, Above 120 and below 130, Above 1 and below 125, Above 10 and below 125, Above 50 and below 125, Above 60 and below 125, Above 70 and below 125, Above 90 and below 125, Above 100 and below 125, Above 110 and below 125, Above 120 and below 125, 1 to 125, 10 to 125, 50 to 125, 60 to 125, 70 to 125, 90 to 125, 100 to 125, 110 to 125, 120 to 125, 1 to 120, 10 to 120, 50 to 120, 60 to 120, 70 to 120, 90 to 120, 100 to 120, 110 to 120, 1 to 110, 10 to 110, 50 to 110, 60 to 110, 70 to 110, 90 to 110, 100 to 110, 100 to 110, 100 to 100, 10 to 100, 50 to 100, 60 to 100, 70 to 100, 90 to 100, etc.

[0031] In determining whether the thermal spraying slurry satisfies the relationship of formula (1), in the calculation of the left side of formula (1), values ​​to the first decimal place with the second decimal place rounded off are prepared and used as E, α, and D90.

[0032] (Spraying particles)

[0033] The oxide containing aluminum that constitutes the spraying particles formed by the oxide containing aluminum is not particularly limited. The oxide containing aluminum can be aluminum oxide (Al2O3), or it can be an oxide containing elements other than aluminum (Al) and oxygen (O) in addition to aluminum (Al). There are no particular restrictions on the elements other than aluminum (Al) and oxygen (O), and examples thereof include rare earth elements, silicon (Si), manganese (Mn), zirconium (Zr), titanium (Ti), chromium (Cr), molybdenum (Mo), platinum (Pt), iridium (Ir), zinc (Zn), calcium (Ca), sodium (Na), phosphorus (P), fluorine (F), boron (B), etc. The elements other than aluminum (Al) and oxygen (O) may contain only one, or may contain two or more. Rare earth elements include scandium (Sc), yttrium (Y), lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), promethium (Pm), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb), and lutetium (Lu). The rare earth elements may contain only one type or two or more types. The oxide containing aluminum is preferably aluminum oxide, or an oxide containing aluminum (Al) and at least one selected from the group consisting of rare earth elements, silicon (Si), manganese (Mn), zirconium (Zr), titanium (Ti), chromium (Cr), molybdenum (Mo), platinum (Pt), iridium (Ir), zinc (Zn), calcium (Ca), sodium (Na), phosphorus (P), fluorine (F) and boron (B), more preferably aluminum oxide, or an oxide containing aluminum (Al) and a rare earth element, further preferably aluminum oxide, or an oxide containing aluminum (Al) and yttrium (Y), further preferably an oxide containing aluminum (Al) and yttrium (Y), and particularly preferably a composite oxide of aluminum (Al) and yttrium (Y). As an oxide containing aluminum (Al) and yttrium (Y), a composite oxide of aluminum (Al) and yttrium (Y) is particularly preferred. As a specific example of a composite oxide of aluminum (Al) and yttrium (Y), there is no particular limitation, for example, yttrium aluminum garnet (Y3Al5O 12 ) (abbreviated as YAG), yttrium aluminum perovskite (YAlO3) (abbreviated as YAP), yttrium aluminum monoclinic (Y4Al2O9) (abbreviated as YAM), etc. As a specific example, the oxide containing aluminum is preferably aluminum oxide (Al2O3), YAG, YAP or YAM, more preferably YAG, YAP or YAM, and further preferably YAG.

[0034] The Young's modulus (E) at a temperature of 25°C containing an oxide of aluminum is not particularly limited. The Young's modulus (E) at a temperature of 25°C containing an oxide of aluminum is preferably 100.0GPa or more, more preferably 150.0GPa or more, and further preferably 180.0GPa or more. If it is within these ranges, there is a tendency that cracks are more likely to occur in the sprayed coating, and therefore, the present invention can be used more effectively. The Young's modulus (E) at a temperature of 25°C containing an oxide of aluminum is preferably 500.0GPa or less, more preferably 400.0GPa or less, further preferably 350.0GPa or less, further preferably 300.0GPa or less, further preferably 250.0GPa or less, and particularly preferably 220.0GPa or less. If it is within these ranges, there is a tendency that cracks are less likely to occur in the sprayed coating. Examples of preferred ranges of the Young's modulus (E) of the oxide containing aluminum at a temperature of 25°C include 100.0 GPa to 500.0 GPa, 150.0 GPa to 400.0 GPa, 180.0 GPa to 350.0 GPa, 180.0 GPa to 300.0 GPa, 180.0 GPa to 250.0 GPa, 180.0 GPa to 220.0 GPa, etc.

[0035] The Young's modulus (E) of an oxide containing aluminum at a temperature of 25°C can be evaluated by the following method. Sprayed particles formed of an oxide containing aluminum are mixed with an aqueous solution of an organic binder (manufactured by KURARAY CO., LTD., Poval (registered trademark): 3-98) in an amount of 2 parts by mass of the organic binder in terms of solid content relative to 100 parts by mass of the sprayed particles, and the obtained mixture is dried to obtain a powder. The obtained powder is uniaxially pressed under a pressure of 50 MPa to produce a molded body. The prepared molded body is sintered at 1600°C and in atmospheric pressure for 12 hours to obtain a block. The obtained block is cut to obtain a test piece (a shape with a diameter of 15 mm and a thickness of 3 mm). For the obtained test piece, at a temperature of 25°C, an ultrasonic thickness meter (manufactured by Olympus Corporation, 38DL PLUS) is used to measure according to the ultrasonic pulse method in accordance with JIS R1602:1995 "Test method for elastic modulus of fine ceramics".

[0036] The linear thermal expansion coefficient (α) of the aluminum oxide in the temperature range of 30°C to 600°C is not particularly limited. The linear thermal expansion coefficient (α) of the aluminum oxide in the temperature range of 30°C to 600°C is preferably 1.0 ppm / K or more, more preferably 5.0 ppm / K or more, further preferably 6.9 ppm / K or more, and particularly preferably 8.0 ppm / K or more. If it is within these ranges, there is a tendency for cracks to become more easily generated in the sprayed coating, and therefore, the present invention can be used more effectively. The linear thermal expansion coefficient (α) of the aluminum oxide in the temperature range of 30°C to 600°C is preferably 20.0 ppm / K or less, more preferably 15.0 ppm / K or less, further preferably 11.0 ppm / K or less, and particularly preferably 10.0 ppm / K or less. If it is within these ranges, there is a tendency for cracks to become less likely to occur in the sprayed coating. Examples of preferred ranges of the coefficient of linear thermal expansion (α) of aluminum oxides in the temperature range of 30°C to 600°C include 1.0 ppm / K to 20.0 ppm / K, 5.0 ppm / K to 15.0 ppm / K, 6.9 ppm / K to 15.0 ppm / K, 6.9 ppm / K to 11.0 ppm / K, 8.0 ppm / K to 11.0 ppm / K, 8.0 ppm / K to 10.0 ppm / K, etc.

[0037] The linear thermal expansion coefficient represents the average linear expansion coefficient measured by a differential expansion thermomechanical analyzer in a predetermined temperature range. The linear thermal expansion coefficient in the temperature range of 30°C to 600°C is a value calculated by dividing the ratio of the change in the length of the test piece in the temperature range of 30°C to 600°C to the initial length (30°C) of the test piece (the change in the length of the test piece in the temperature range of 30°C to 600°C / the initial length (30°C) of the test piece) by the measured temperature difference. The linear thermal expansion coefficient (α) in the temperature range of 30°C to 600°C of an oxide containing aluminum can be evaluated by the following method. Spraying particles formed of an oxide containing aluminum and an aqueous solution of an organic binder (manufactured by KURARAY CO., LTD., Poval (registered trademark): 3-98) are mixed in an amount of 2 parts by mass of the organic binder in terms of solid content relative to 100 parts by mass of the spraying particles, and the obtained mixture is dried to obtain a powder. The obtained powder is uniaxially pressed at a pressure of 50 MPa to produce a molded body. The molded body was fired at 1600°C for 12 hours in atmospheric pressure to obtain a block. The obtained block was cut to obtain a test piece (5mm×5mm×10mm prism). The test piece obtained above was measured using a thermomechanical analyzer (TD5200SA manufactured by NETZSCH Japan Co., Ltd.) in accordance with JIS R 1618:2002 "Method for measuring thermal expansion of fine ceramics based on thermomechanical analysis", thereby obtaining the linear thermal expansion coefficient (α) of the oxide containing aluminum in the temperature range of 30°C to 600°C.

[0038] The shape of the thermal spray particles formed of an oxide containing aluminum is not limited to a sphere or a shape close thereto, and may be various forms such as a substantially spherical shape, a needle shape, a rod shape, a flaky shape, a cubic shape, or an amorphous shape.

[0039] In this specification, the volume-based cumulative 90% particle size (D90) refers to the particle size at which the cumulative frequency from the small particle size side becomes 90% in the volume-based cumulative particle size distribution based on the laser diffraction scattering particle size distribution measurement method. The volume-based cumulative 90% particle size (D90) of the sprayed particles formed by the oxide containing aluminum is not particularly limited. The volume-based cumulative 90% particle size (D90) of the sprayed particles formed by the oxide containing aluminum is preferably 30.0 μm or less, more preferably 20.0 μm or less, further preferably 17.0 μm or less, and particularly preferably 15.0 μm or less. If it is within these ranges, there is a tendency for cracks to become more likely to occur in the sprayed coating, and therefore, the present invention can be used more effectively. In addition, if it is within these ranges, there is a tendency for the surface roughness and / or porosity in the coating to be further reduced. The volume-based cumulative 90% particle size (D90) of the sprayed particles formed by oxides containing aluminum is preferably greater than 6.2μm, more preferably greater than 10.0μm, and further preferably greater than 10.5μm. If it is within these ranges, there is a tendency for cracks to become less likely to occur in the sprayed coating. Examples of preferred ranges of the volume-based cumulative 90% particle size (D90) of the sprayed particles formed by oxides containing aluminum include greater than 6.2μm and less than 30.0μm, greater than 6.2μm and less than 20.0μm, greater than 10.0μm and less than 17.0μm, greater than 10.5μm and less than 15.0μm, etc. In the case where the sprayed particles are formed by aluminum oxide, there is no particular restriction on the volume-based cumulative 90% particle size (D90) of the sprayed particles, and it is particularly preferred to be greater than 6.2μm. Examples of preferred ranges of the volume-based cumulative 90% particle size (D90) of thermal spray particles formed of aluminum oxide include more than 6.2 μm and less than 30.0 μm, more than 6.2 μm and less than 20.0 μm, more than 10.0 μm and less than 30.0 μm, more than 10.0 μm and less than 20.0 μm, more than 10.5 μm and less than 30.0 μm, more than 10.5 μm and less than 20.0 μm, etc. When the thermal spray particles are formed of an oxide containing aluminum (Al) and yttrium (Y), the volume-based cumulative 90% particle size (D90) of the thermal spray particles is not particularly limited, but is particularly preferably more than 10.0 μm. Examples of preferred ranges of the volume-based cumulative 90% particle size (D90) of sprayed particles formed by oxides containing aluminum (Al) and yttrium (Y) include greater than 10.0 μm and less than 30.0 μm, greater than 10.0 μm and less than 20.0 μm, greater than 10.0 μm and less than 17.0 μm, greater than 10.0 μm and less than 15.0 μm, greater than 10.5 μm and less than 30.0 μm, greater than 10.5 μm and less than 20.0 μm, greater than 10.5 μm and less than 17.0 μm, greater than 10.5 μm and less than 15.0 μm, etc.

[0040] In this specification, the volume-based cumulative 10% particle size (D10) refers to the particle size at which the cumulative frequency from the small particle size side in the volume-based cumulative particle size distribution based on the laser diffraction scattering particle size distribution measurement method becomes 10%, and the volume-based cumulative 50% particle size (D50) refers to the particle size at which the cumulative frequency from the small particle size side in the volume-based cumulative particle size distribution based on the laser diffraction scattering particle size distribution measurement method becomes 50%. The volume-based cumulative 10% particle size (D10) of the thermal spraying particles formed of an oxide containing aluminum is not particularly limited, but is preferably greater than 1.8 μm and less than 5.0 μm, more preferably greater than 1.8 μm and less than 4.0 μm, and further preferably greater than 1.9 μm and less than 3.5 μm. The volume-based cumulative 50% particle size (D50) of the thermal spraying particles formed of an oxide containing aluminum is not particularly limited, but is preferably greater than 3.5 μm and less than 9.0 μm, more preferably greater than 4.5 μm and less than 9.0 μm, and further preferably greater than 4.5 μm and less than 9.0 μm.

[0041] The volume-based cumulative 10% particle size (D10) of the thermal spraying particles formed of an oxide containing aluminum, the volume-based cumulative 50% particle size (D50) of the thermal spraying particles formed of an oxide containing aluminum, and the volume-based cumulative 90% particle size (D90) of the thermal spraying particles formed of an oxide containing aluminum can be measured by a laser diffraction scattering particle size distribution measurement method. More specifically, the volume-based particle size distribution in the thermal spraying slurry containing the thermal spraying particles formed of an oxide containing aluminum is measured using a laser diffraction particle size distribution measurement device, and in the obtained particle size distribution, the particle sizes at which the cumulative values ​​from the small particle size side are 10%, 50%, and 90% are obtained, and these particle sizes are respectively defined as the volume-based cumulative 10% particle size (D10), the volume-based cumulative 50% particle size (D50), and the volume-based cumulative 90% particle size (D90).

[0042] The volume-based cumulative 10% particle size (D10) of the spraying particles formed by the oxide containing aluminum, the volume-based cumulative 50% particle size (D50) of the spraying particles formed by the oxide containing aluminum, and the volume-based cumulative 90% particle size (D90) of the spraying particles formed by the oxide containing aluminum can be controlled by, for example, the crushing conditions of the particles. For example, these particle sizes can be reduced by increasing the pressure of the high-pressure air introduced into the crushing chamber. When two or more particles (powders) with different particle size distributions are mixed, these particle sizes can also be controlled by their mixing ratio. However, the method for controlling these particle sizes is not particularly limited.

[0043] As the thermal spray particles, commercially available products may be used, particles obtained by processing commercially available products may be used, or synthetic products may be used.

[0044] The content of the spraying particles in the spraying slurry of this mode is not particularly limited. The content of the spraying particles in the spraying slurry of this mode is not particularly limited as long as it exceeds 0 mass % relative to the total mass of the spraying slurry, preferably 1 mass % or more, more preferably 2 mass % or more, further preferably 3 mass % or more, particularly preferably 4 mass % or more relative to the total mass of the spraying slurry. If it is these ranges, there is a tendency to become more prone to cracks in the spraying coating, so the present invention can be used more effectively. The content of the spraying particles in the spraying slurry of this mode is preferably less than 55 mass %, more preferably less than 51 mass %, further preferably less than 50 mass %, further preferably less than 49 mass %, further preferably less than 31 mass %, further preferably less than 30 mass %, further preferably less than 11 mass %, particularly preferably less than 10 mass %. If it is these ranges, there is a tendency to become less prone to cracks in the spraying coating. Examples of preferred ranges of the content of the spraying particles in the spraying slurry of the present embodiment include more than 0 mass % and less than 55 mass %, more than 0 mass % and less than 51 mass %, more than 0 mass % and less than 50 mass %, more than 0 mass % and less than 49 mass %, more than 1 mass % and less than 31 mass %, more than 1 mass % and less than 30 mass %, more than 2 mass % and less than 11 mass %, more than 2 mass % and less than 10 mass %, more than 3 mass % and less than 11 mass %, more than 3 mass % and less than 10 mass %, more than 3 mass % and less than 11 mass %, more than 3 mass % and less than 10 mass %, more than 4 mass % and less than 10 mass %, etc., relative to the total mass of the spraying slurry.

[0045] (Dispersion Medium)

[0046] There is no particular limitation on the dispersion medium. In the spray slurry, the spray particles are dispersed in the dispersion medium. When the spray slurry contains other components described later, the dispersion medium can also disperse or dissolve the other components. As the dispersion medium, for example, water, an organic solvent or a combination thereof can be cited. As the organic solvent, there is no particular limitation, for example, alcohols such as methanol, ethanol, isopropanol, toluene, hexane, kerosene, etc. can be cited. The dispersion medium preferably contains water. The dispersion medium is particularly preferably water.

[0047] (Other ingredients)

[0048] The spraying slurry of this embodiment may further contain components other than the spraying particles and the dispersion medium formed by the oxide containing aluminum (in this specification, the components other than the spraying particles and the dispersion medium formed by the oxide containing aluminum are also referred to as "other components"). There are no particular restrictions on other components, and examples thereof include pH adjusters, dispersants, viscosity adjusters, defoamers, preservatives, mildew inhibitors, and flocculants. Other components may contain only one component or may contain two or more components.

[0049] The spraying slurry of this mode preferably also contains a dispersant. The dispersant refers to a component that can improve the dispersion stability of the spraying particles in the spraying slurry. The dispersant is not particularly limited. As a dispersant, anionic dispersants, cationic dispersants, and nonionic dispersants can be cited. As specific examples of anionic dispersants, polycarboxylic acid dispersants, naphthalenesulfonic acid dispersants, alkylsulfonic acid dispersants, polyphosphoric acid dispersants, etc. can be cited. As specific examples of cationic dispersants, polyalkylene polyamine dispersants, quaternary ammonium dispersants, alkyl polyamine dispersants, imidazoline dispersants, etc. can be cited. As specific examples of nonionic dispersants, alkylene oxide dispersants, polyol ester dispersants, etc. can be cited. As polycarboxylic acid dispersants, for example, polycarboxylic acid sodium salts (another name: sodium polycarboxylates), polycarboxylic acid ammonium salts (another name: ammonium polycarboxylates), etc. can be cited. As the naphthalenesulfonic acid dispersant, for example, naphthalenesulfonic acid sodium salt (another name: sodium naphthalenesulfonate), naphthalenesulfonic acid ammonium salt (another name: ammonium naphthalenesulfonate) etc. can be mentioned. As the imidazoline dispersant, alkyl imidazoline etc. can be mentioned. The dispersant preferably contains at least one selected from the group consisting of anionic dispersants, cationic dispersants and nonionic dispersants, more preferably contains anionic dispersants, further preferably contains at least one selected from the group consisting of polycarboxylic acid dispersants, naphthalenesulfonic acid dispersants, alkylsulfonic acid dispersants and polyphosphoric acid dispersants, further preferably contains polycarboxylic acid dispersants, further preferably contains at least one selected from the group consisting of sodium polycarboxylates and ammonium polycarboxylates, and particularly preferably contains ammonium polycarboxylates.

[0050] The dispersant may be contained alone or in combination of two or more.

[0051] The content of the dispersant in the spraying slurry of the present mode is not particularly limited. For the content of the dispersant in the spraying slurry of the present mode, relative to 100 parts by mass of the spraying particles, it is preferably 0.001 parts by mass or more, more preferably 0.01 parts by mass or more, and further preferably 0.02 parts by mass or more, calculated on a solid basis. If it is within these ranges, the flocculation of the spraying particles contained in the slurry can be further suppressed. The content of the dispersant in the spraying slurry of the present mode is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, and further preferably 1 part by mass or less, calculated on a solid basis, relative to 100 parts by mass of the spraying particles. If it is within these ranges, the occurrence of reflocculation can be further suppressed, and the maintainability of the state in which the spraying particles are dispersed can be further improved. Preferred examples of the content of the dispersant in the spray slurry of this embodiment include 0.001 to 10 parts by mass, 0.01 to 5 parts by mass, 0.02 to 1 part by mass, etc., calculated as solid content relative to 100 parts by mass of the spray particles. When two or more dispersants are used in combination, the content of the dispersant refers to the total content of the two or more dispersants.

[0052] The total content of the spraying particles, dispersant and dispersion medium in the spraying slurry of this embodiment is preferably more than 99% by mass (upper limit: 100% by mass) relative to the total mass of the spraying slurry. The total content of the spraying particles, dispersant and dispersion medium in the spraying slurry of this embodiment can be 100% by mass relative to the total mass of the spraying slurry.

[0053] (Solid content concentration)

[0054] The solid content concentration of the spraying slurry of this mode is not particularly limited. The solid content concentration of the spraying slurry of this mode is preferably more than 1% by mass, more preferably more than 2% by mass, further preferably more than 4% by mass, and particularly preferably more than 5% by mass. If it is these ranges, there is a tendency to become more prone to cracks in the spray coating, so the present invention can be used more effectively. The solid content concentration of the spraying slurry of this mode is preferably less than 55% by mass, more preferably less than 51% by mass, further preferably less than 50% by mass, further preferably less than 31% by mass, further preferably less than 30% by mass, further preferably less than 11% by mass, and particularly preferably less than 10% by mass. If it is these ranges, there is a tendency to become less prone to cracks in the spray coating. Examples of preferred ranges of solid content concentration in the spraying slurry of the present embodiment include 1% by mass to 55% by mass, 1% by mass to 51% by mass, 1% by mass to 50% by mass, 2% by mass to 31% by mass, 2% by mass to 30% by mass, 4% by mass to 11% by mass, 4% by mass to 10% by mass, 5% by mass to 10% by mass, etc.

[0055] The solid content concentration of the thermal spraying slurry can be calculated from the mass (total mass) of the thermal spraying slurry and the mass of the solid content residue obtained by drying the manufactured thermal spraying slurry.

[0056] (Method for producing thermal spray slurry)

[0057] The method for manufacturing the spraying slurry of this mode is not particularly limited. The spraying slurry can be manufactured by mixing a dispersion medium with spraying particles formed by an oxide containing aluminum and other components added as needed. The mixing can be carried out using a blade stirrer, a homogenizer or a mixer.

[0058] (Base material)

[0059] The thermal spray slurry is preferably used for forming a thermal spray coating. When the thermal spray slurry is thermally sprayed onto a substrate, a thermal spray coating is formed on the substrate.

[0060] The material of substrate is not particularly limited. As substrate, for example, a metal substrate, an alloy substrate, a ceramic substrate, etc. can be cited. As a specific example of the material of substrate, aluminum, aluminum alloy, iron, steel, copper, copper alloy, nickel, nickel alloy, gold, silver, bismuth, manganese, zinc, zinc alloy, etc. can be cited. Among these, a substrate formed by steel represented by stainless steel, a substrate formed by a heat-resistant alloy represented by Inconel, a low expansion alloy substrate represented by Invar or Kovar, a corrosion-resistant alloy substrate represented by Hastelloy, and a substrate formed by aluminum or aluminum alloy can be cited as a preferred example. By using these substrates, there is a tendency that the crack reduction effect of the spray coating is further improved. The reason is as follows. The thermal expansion coefficient of these substrates is large. Thus, after these substrates expand due to the heat of spraying, when shrinkage occurs after the spraying ends, the shrinkage of these substrates also becomes larger. As a result, the thermal stress generated between the spray coating and the substrate becomes easy to reduce. Among these, a metal substrate or an alloy substrate is preferred, and a substrate formed of aluminum or an aluminum alloy is particularly preferred. The substrate formed of aluminum or an aluminum alloy is not particularly limited, and examples thereof include Al6061, Al6063, and the like.

[0061] (Spraying method and method for producing sprayed coating)

[0062] The method of spraying the spray slurry of this method may be high-speed flame spraying in which the spray slurry is supplied to the center of a high-speed combustion flame jet generated by high-pressure oxygen (or air) and fuel and continuously sprayed at high speed, such as high-speed oxygen fuel spraying (HVOF). The method of spraying the spray slurry of this method may be plasma spraying in which the spray slurry is supplied to the center of a plasma jet generated by a gas that becomes plasma and sprayed, such as atmospheric plasma spraying (APS: atmospheric plasma spraying) performed in the atmosphere, low-pressure plasma spraying (LPS: low pressure plasma spraying) performed at a pressure lower than the atmospheric pressure, or pressurized plasma spraying (high pressure plasma spraying) performed in a pressurized container higher than the atmospheric pressure. If the spray slurry of this method is sprayed by high-speed flame spraying or plasma spraying, the spray slurry with a high content of ceramic particles can be sprayed with good fluidity, and a dense spray coating can be formed efficiently.

[0063] The spraying distance, i.e., the distance from the nozzle front end of the spraying device to the substrate is not particularly limited. The spraying distance is preferably more than 60 mm. In this case, it becomes easy to suppress thermal deterioration and thermal deformation of the substrate. The spraying distance is also preferably less than 200 mm. In this case, the spraying particles are fully heated during spraying, thereby becoming easy to obtain a dense spray coating. Thus, as a preferred example of the spraying distance, more than 60 mm and less than 200 mm can be cited.

[0064] The thermal spraying slurry of this embodiment is preferably used for high velocity flame spraying or plasma spraying, and more preferably used for plasma spraying.

[0065] During spraying, it is preferred to spray water around the spray jet to cool the periphery of the spray jet from the periphery. During plasma spraying, it is particularly preferred to spray water around the plasma jet to cool the periphery of the plasma jet. The water sprayed around the spray jet is preferably carried out using a water shield device, and the water sprayed around the plasma jet is particularly preferably carried out using a water shield device. The water shield device is arranged closer to the substrate side than the supply nozzle of the spray slurry. Usually, the water shield is annular, and the spray jet (such as a plasma jet, etc.) and the supplied spray slurry are passed through the inside thereof. A plurality of water injection ports are provided on the inner side of the water shield device, so water is supplied from a water supply port different from the water injection port, thereby radiating cooling water from the water injection port to the spray jet (such as a plasma jet, etc.). As a result, the particles that are not fully melted in the periphery of the spray jet (such as a plasma jet, etc.) become non-melted and are not incorporated into the coating, so that it is possible to improve the density of the coating.

[0066] The spraying slurry of this mode is preferably used for spraying while spraying water around the spraying jet. In this application, the spraying slurry is supplied to the spraying jet, and water is sprayed around the spraying jet to which the spraying slurry is supplied. The spraying slurry of this mode is particularly preferably used for plasma spraying while spraying water around the plasma jet. In this application, the spraying slurry is supplied to the plasma jet, and water is sprayed around the plasma jet to which the spraying slurry is supplied. In these sprayings, the insufficiently melted particles at the periphery of the spraying slurry and the spraying jet (particularly preferably the plasma jet) are cooled and become non-molten, and the deposition of the insufficiently melted particles on the substrate is suppressed, and the fully melted particles mainly passing through the center of the spraying jet (particularly preferably the plasma jet) can be made to collide with the surface of the substrate. As a result, in such spraying, it is possible to improve the density of the coating.

[0067] Therefore, another embodiment of the present invention can also be said to relate to a method for manufacturing a spray coating, which includes the step of spraying the spray slurry of the above embodiment. According to this embodiment, cracks in a spray coating formed using a spray slurry containing spray particles formed of an oxide containing aluminum can be reduced. The description of the spray method in this embodiment is the same as the description of the spray method of the spray slurry of the above embodiment. The method for manufacturing a spray coating of this embodiment preferably includes the step of spraying a metal substrate or an alloy substrate, and particularly preferably includes the step of spraying a substrate formed of aluminum or an aluminum alloy. The method for manufacturing a spray coating of this embodiment preferably includes: the step of supplying the spray slurry of the above embodiment to a spray jet; and, the step of spraying the spray slurry while spraying water around the aforementioned spray jet. The method for manufacturing a spray coating of this embodiment particularly preferably includes: the step of supplying the spray slurry of the above embodiment to a plasma jet; and, the step of spraying the plasma of the spray slurry while spraying water around the plasma jet.

[0068] The embodiments of the present invention have been described in detail, but these are illustrative and exemplary and not limiting. Obviously, the protection scope of the present invention should be interpreted by the appended claims.

[0069] The present invention includes the following modes and aspects:

[0070] [1] A thermal spraying slurry comprising: thermal spraying particles formed of an oxide containing aluminum and a dispersion medium,

[0071] The above-mentioned spraying slurry satisfies the following formula (1):

[0072] (E×α) / D90<130…(1)

[0073] In the above formula (1),

[0074] E is the Young's modulus of the oxide at 25°C [unit: GPa],

[0075] α is the linear thermal expansion coefficient of the aforementioned oxide in the temperature range of 30°C to 600°C [unit: ppm / K],

[0076] D90 is the volume-based cumulative 90% particle size of the thermal spray particles [unit: μm].

[0077] [2] The thermal spraying slurry according to [1] above, wherein the solid content concentration of the thermal spraying slurry is 55% by mass or less.

[0078] [3] The thermal spraying slurry according to [1] or [2], further comprising a dispersant.

[0079] [4] The thermal spraying slurry according to any one of [1] to [3] above, wherein the oxide is an oxide containing aluminum and yttrium.

[0080] [5] The thermal spraying slurry according to any one of [1] to [4], which is used for thermal spraying performed while spraying water around a thermal spray jet.

[0081] [6] A method for producing a thermal spray coating, comprising the step of thermally spraying the thermal spray slurry according to any one of [1] to [5] above.

[0082] Example

[0083] The present invention is further described in detail with the following examples and comparative examples. However, the protection scope of the present invention should not be limited to the following examples.

[0084] <Spraying slurry>

[0085] (Manufacturing of Spraying Slurry of Example 1)

[0086] The spraying particles were prepared as follows: commercially available Y3Al5O 12 (YAG) particles (D50: 25 μm) were crushed with a horizontal jet mill to prepare the spraying slurry of Example 1. The obtained spraying particles were mixed with a dispersant containing ammonium polycarboxylate and water as a dispersion medium so that the content of the spraying particles was 10% by mass relative to the total mass of the spraying slurry and the content of the dispersant was 0.05 parts by mass relative to 100 parts by mass of the spraying particles in terms of solid content conversion.

[0087] (Manufacturing of Spraying Slurry of Example 2)

[0088] The thermal spraying slurry of Example 2 was produced in the same manner as in the production of the thermal spraying slurry of Example 1, except that the pulverization conditions were changed so as to obtain the particle diameter of the thermal spraying particles described in Table 1 to produce the thermal spraying particles.

[0089] (Manufacturing of Spraying Slurry of Examples 3 and 4 and Comparative Example 1)

[0090] The pulverizing conditions were changed so as to obtain the particle size of the spraying particles recorded in Table 1, and the spraying particles were prepared so that the content of the spraying particles was 30 mass % relative to the total mass of the spraying slurry, and the content of the dispersant was 0.05 mass part relative to 100 mass parts of the spraying particles in terms of solid content. Except for this, the spraying slurries of Examples 3 and 4 and Comparative Example 1 were prepared in the same manner as the preparation of the spraying slurry of Example 1.

[0091] (Manufacturing of Spraying Slurry of Example 5 and Comparative Example 2)

[0092] The pulverizing conditions were changed in such a way that the particle size of the spraying particles recorded in Table 1 was obtained, and the spraying particles were prepared so that the content of the spraying particles was 50 mass % relative to the total mass of the spraying slurry, and the content of the dispersant was 0.05 mass parts relative to 100 mass parts of the spraying particles in terms of solid content. Except for this, the spraying slurries of Example 5 and Comparative Example 2 were prepared in the same manner as the preparation of the spraying slurry of Example 1.

[0093] (Manufacturing of Spraying Slurry of Example 6)

[0094] Commercially available Al2O3 particles A (D50: 3±0.4 μm) and commercially available Al2O3 particles B (D50: 9.9±0.8 μm) were prepared at a ratio (mass ratio) of A:B=4:6. The two kinds of Al2O3 particles were mixed with a dispersant containing ammonium polycarboxylate and water as a dispersion medium in such a manner that the total content of the two kinds of commercially available Al2O3 particles was 30% by mass relative to the total mass of the spraying slurry and the content of the dispersant was 0.05 parts by mass relative to the total amount of 100 parts by mass of the two kinds of commercially available Al2O3 particles in terms of solid content conversion, to produce the spraying slurry of Example 6. It should be noted that in the present spraying slurry, the spraying particles are Al2O3 particles obtained by mixing two kinds of commercially available Al2O3 particles at the above ratio (mass ratio).

[0095] (Manufacturing of Spraying Slurry of Comparative Example 3)

[0096] Commercially available Al2O3 particles (D50: 3±0.4 μm) were prepared as spraying particles. The spraying particles were mixed with a dispersant containing ammonium polycarboxylate and water as a dispersion medium so that the content of the spraying particles was 30% by mass relative to the total mass of the spraying slurry and the content of the dispersant was 0.05 parts by mass relative to 100 parts by mass of the commercially available spraying particles in terms of solid content, to prepare a spraying slurry of Comparative Example 3.

[0097] (Solid content concentration of spraying slurry)

[0098] The solid content concentration of the spraying slurry produced above was calculated from the mass (total mass) of the spraying slurry and the mass of the solid content residue obtained by drying the spraying slurry at 105° C. The solid content concentrations of the respective spraying slurries are shown in Table 1. It should be noted that the solid content concentrations described in Table 1 are values ​​calculated by rounding off the first decimal place.

[0099] (Young's modulus at 25°C including aluminum oxide)

[0100] The Young's modulus (E) [unit: GPa] of the aluminum oxide constituting the sprayed particles at a temperature of 25°C is evaluated as follows. The sprayed particles formed of aluminum oxide are mixed with an aqueous solution of an organic binder (manufactured by KURARAY CO., LTD., Poval (registered trademark): 3-98) in an amount of 2 parts by mass of the organic binder in terms of solid content relative to 100 parts by mass of the sprayed particles, and the obtained mixture is dried to obtain a powder. The obtained powder is uniaxially pressed at a pressure of 50 MPa to produce a molded body. The prepared molded body is sintered at 1600°C and in atmospheric pressure for 12 hours to obtain a block. The obtained block is cut to obtain a test piece (a shape with a diameter of 15 mm and a thickness of 3 mm). The obtained test piece was measured at a temperature of 25°C using an ultrasonic thickness meter (38DLPLUS manufactured by Olympus Corporation) according to JIS R1602:1995 "Test method for elastic modulus of fine ceramics" by an ultrasonic pulse method, and the obtained value was defined as the Young's modulus (E) of the oxide containing aluminum at a temperature of 25°C. The obtained values ​​are shown in Table 1.

[0101] In addition, in this evaluation, the porosity of the test pieces of Examples 1 to 6 and Comparative Examples 1 to 3 measured by the Archimedean method was 3.9% by volume.

[0102] (Linear thermal expansion coefficient of aluminum oxide in the temperature range of 30°C to 600°C)

[0103] As described above, the linear thermal expansion coefficient in the temperature range of 30°C to 600°C is a value calculated by dividing the ratio of the change in the length of the test piece in the temperature range of 30°C to 600°C to the initial length (30°C) of the test piece (change in the length of the test piece in the temperature range of 30°C to 600°C / initial length (30°C) of the test piece) by the measured temperature difference. The linear thermal expansion coefficient (α) [unit: ppm / K] of the oxide containing aluminum constituting the thermal spray particles in the temperature range of 30°C to 600°C is evaluated as follows. The thermal spray particles formed of the oxide containing aluminum and an aqueous solution of an organic binder (manufactured by KURARAY CO., LTD., Poval (registered trademark): 3-98) are mixed in an amount of 2 parts by mass of the organic binder in terms of solid content relative to 100 parts by mass of the thermal spray particles, and the obtained mixture is dried to obtain a powder. The obtained powder is uniaxially pressed at a pressure of 50 MPa to produce a molded body. The molded body was fired at 1600°C for 12 hours in atmospheric pressure to obtain a block. The obtained block was cut to obtain a test piece (5mm×5mm×10mm prism). The temperature range was 30°C to 600°C, and the test piece obtained above was measured using a thermomechanical analyzer (TD5200SA manufactured by NETZSCH Japan Co., Ltd.) according to JIS R 1618:2002 "Method for determination of thermal expansion of fine ceramics based on thermomechanical analysis", thereby obtaining the linear thermal expansion coefficient (α) [unit: ppm / K] of the oxide containing aluminum in the temperature range of 30°C to 600°C. The obtained values ​​are shown in Table 1.

[0104] In addition, in this evaluation, the porosity of the test pieces of Examples 1 to 6 and Comparative Examples 1 to 3 measured by the Archimedean method was 3.9% by volume.

[0105] (Spraying particle size)

[0106] As described above, the volume-based cumulative 10% particle size (D10) refers to the particle size at which the cumulative frequency from the small particle size side becomes 10% in the volume-based cumulative particle size distribution based on the laser diffraction scattering particle size distribution measurement method, the volume-based cumulative 50% particle size (D50) refers to the particle size at which the cumulative frequency from the small particle size side becomes 50% in the volume-based cumulative particle size distribution based on the laser diffraction scattering particle size distribution measurement method, and the volume-based cumulative 90% particle size (D90) refers to the particle size at which the cumulative frequency from the small particle size side becomes 90% in the volume-based cumulative particle size distribution based on the laser diffraction scattering particle size distribution measurement method.

[0107] The volume-based particle size distribution in the thermal spraying slurry was measured using a laser diffraction particle size distribution measuring device (Mastersizer 3000 manufactured by Malvern Panalytical). In the particle size distribution, the particle sizes at which the cumulative values ​​from the small particle size side are 10%, 50%, and 90% were obtained, and these particle sizes were respectively used as the volume-based cumulative 10% particle size (D10) [unit: μm] of the thermal spraying particles, the volume-based cumulative 50% particle size (D50) [unit: μm] of the thermal spraying particles, and the volume-based cumulative 90% particle size (D90) [unit: μm] of the thermal spraying particles. The obtained values ​​are shown in Table 1.

[0108] (Confirmation of the relationship in formula (1))

[0109] For the thermal spraying slurry produced above, the calculated value of the left side of the formula (1) was calculated using the values ​​obtained in the above measurements to confirm whether the thermal spraying slurry produced above satisfies the relationship of the formula (1).

[0110] (E×α) / D90<130…(1)

[0111] E: Young's modulus of the oxide containing aluminum constituting the thermal spray particles at a temperature of 25°C [unit: GPa],

[0112] α: linear thermal expansion coefficient of the oxide containing aluminum constituting the thermal spray particles in the temperature range of 30° C. to 600° C. [unit: ppm / K],

[0113] D90: Volume-based cumulative 90% particle size of sprayed particles [unit: μm].

[0114] Here, in determining whether the above-produced thermal spraying slurry satisfies the relationship of formula (1), in the calculation of the left side of formula (1), the values ​​of E, α, and D90 are prepared and used by rounding off the second decimal place to the first decimal place. It should be noted that the values ​​of E, α, and D90 prepared in this way to the first decimal place are respectively recorded in Table 1.

[0115] The calculated values ​​of the left side of the formula (1) are shown in Table 1. In addition, in Table 1, the calculation results of the left side of the formula (1) are described as values ​​rounded off to the first decimal place.

[0116] <Spray coating>

[0117] (Manufacturing of thermal spray coating)

[0118] The plasma spraying device 100HE manufactured by Progressive Surface is used to spray the spraying slurry manufactured in the above onto a substrate formed of an aluminum alloy (hereinafter, also referred to as "aluminum alloy substrate"), and a spray coating is manufactured on the aluminum alloy substrate. The supply device for supplying the spraying slurry to the plasma spraying device is the LiquifeederHE (trade name) SPS / SPPS feeding system manufactured by Progressive Surface. The plasma spraying device and a water shield device are used together, and the water shield device is the LiquiEdge (trademark) Thermal Spray Shroud manufactured by Progressive Surface. The water shield device is arranged on the substrate side closer to the supply nozzle of the spraying slurry. Spraying is performed while spraying cooling water from the water injection port of the water shield device to the periphery of the plasma jet. The spraying conditions are set as described below. The film thickness of the obtained sprayed coating is 50μm.

[0119] 《Spraying conditions》

[0120] Argon flow rate: 135NL / min

[0121] Nitrogen flow rate: 52.5NL / min

[0122] Hydrogen flow rate: 52.5NL / min

[0123] Plasma power: 105kW

[0124] Spraying distance: 86 mm (Examples 1-5, Comparative Examples 1-2), 76 mm (Example 6, Comparative Example 3)

[0125] Traverse speed: 1500mm / s

[0126] Spraying angle: 90°

[0127] Slurry supply: 38mL / min

[0128] Substrate: Aluminum alloy substrate (Al6061, 50mm×50mm×5mm).

[0129] (Cracks in the spray coating)

[0130] The surface of the sprayed coating produced above was observed with a digital microscope (VHX-5000) manufactured by KEYENCE CORPORATION at a lens magnification of 30 times to confirm the presence or absence of cracks. The evaluation results are shown in Table 1. In Table 1, the case where cracks were confirmed in the sprayed coating was recorded as "B", and the case where cracks were not confirmed in the sprayed coating was recorded as "A".

[0131] It should be noted that the surface observation image of the thermal spray coating formed by the thermal spray slurry of Example 1 based on the digital microscope is shown in Figure 1 The surface observation image of the spray coating formed by the spray coating slurry of Comparative Example 1 based on a digital microscope is shown in Figure 2 The surface observation image of the spray coating formed by the spray coating slurry of Comparative Example 2 based on a digital microscope is shown in Figure 3 .

[0132] The results in Table 1 show that the occurrence of cracks in the thermal spray coating produced by using the thermal spray slurry of the example containing thermal spray particles and a dispersion medium containing an oxide of aluminum and satisfying the formula (1) is significantly reduced. On the other hand, it is confirmed that cracks are easily generated in the thermal spray coating produced by using the thermal spray slurry of the comparative example that does not satisfy the formula (1).

[0133] [Table 1]

[0134]

[0135] This application is based on Japanese Patent Application No. 2023-170228 filed on September 29, 2023, the disclosure of which is incorporated herein by reference in its entirety.

Claims

1. A slurry for thermal spraying, comprising: thermal spraying particles formed of an oxide containing aluminum and a dispersion medium, The spraying slurry satisfies the following formula (1): (E×α) / D90<130…(1) In the formula (1), E is the Young's modulus of the oxide at a temperature of 25°C [unit: GPa], α is the linear thermal expansion coefficient of the oxide in the temperature range of 30° C. to 600° C. [unit: ppm / K], D90 is the volume-based cumulative 90% particle size of the sprayed particles [unit: μm].

2. The spraying slurry according to claim 1, wherein The solid content concentration of the thermal spraying slurry is 55 mass % or less. The thermal spraying slurry according to claim 1 , further comprising a dispersant.

4. The spraying slurry according to claim 1, wherein The oxide is an oxide containing aluminum and yttrium.

5. The thermal spraying slurry according to claim 1, which is used for thermal spraying performed while spraying water around a thermal spray jet. 6 . A method for producing a thermal spray coating, comprising the step of: thermally spraying the thermal spray slurry according to claim 1 .

Citation Information

Patent Citations

  • Thermal-spraying powder and thermal-sprayed film

    JP2002080954A

  • Gas sensor element and manufacturing method therefor

    JP2007298490A

  • Thermal spray coatings for semiconductor applications

    JP2013531135A

  • Image forming system, image forming device, external device, and paper supply device

    JP2023170228A